Odpowiedzi

2010-03-17T19:47:45+01:00
A) -5(-x+1) =5x-5
b) -3a(⅓-a) =-a+3a²
c) (t- 2s - 1) * 7=7t-14s-7
d) ½ (2a-4b+1)=a-2b+1/2
e) m(2m+3) = 2m²+3m
f) 3p(2r+5p-1) = 6pr+15p²-3p
g) xy(2x-3y+5) = 2x²y-3xy²+5xy
2010-03-17T19:49:41+01:00
A) 5x - 5
b) a + 3a(kwadrat)
c) 7t - 14s -7
d) a - 2b + 1/2
e) 2m(kwadrat) + 3m
f) 6pr + 15p(kwadrat) - 3p
g) 2x(kwadrat)y - 3xy(kwadrat) + 5xy
2010-03-17T19:52:44+01:00
A) -5(-x+1)
5x-5

b) -3a(⅓-a)
-a+3a²
c) (t- 2s - 1) * 7
7t-14s-7
d) ½ (2a-4b+1)
a-2b+½
e) m(2m+3)
2m²+3m
f) 3p(2r+5p-1)
6pr+15p²-3p
g) xy(2x-3y+5)
2x²y-3xy²+5xy